Keeping all options open: Parents' approaches to advance care planning. (26th September 2016) - Beecham, Emma; Oostendorp, Linda; Crocker, Joanna; Kelly, Paula; Dinsdale, Andrew; Hemsley, June; Russell, Jessica; Jones, Louise; Bluebond‐Langner, Myra
Abstract: Background: Early engagement in advance care planning (ACP) is seen as fundamental for ensuring the highest standard of care for children and young people with a life‐limiting condition (LLC). However, most families have little knowledge or experience of ACP. Objective: To investigate how parents of children and young people with LLCs approach and experience ACP. Methods: Open‐ended, semi‐structured interviews were conducted with parents of 18 children; nine children who were currently receiving palliative care services, and nine children who had received palliative care and died. Verbatim transcripts of audiotaped interviews were analysed following principles of grounded theory while acknowledging the use of deductive strategies, taking account of both the child's condition, and the timing and nature of decisions made. Results: Parents reported having discussions and making decisions about the place of care, place of death and the limitation of treatment. Most decisions were made relatively late in the illness and by parents who wished to keep their options open. Parents reported different levels of involvement in a range of decisions; many wished to be involved in decision making but did not always feel able to do so. Discussion: This study highlights that parents' approaches to decision making vary by the type of decision required. Their views may change over time, and it is important to allow them to keep their options open. We recommend that clinicians have regular discussions over the course of the illness in an effort to understand parents' approaches to particular decisions rather than to drive to closure prematurely.